Effects of grain species, genotype and starch quantity on the postprandial plasma amino acid response in horses. (June 2018) - Bachmann, Martin; Czetö, Aniko; Romanowski, Kristin; Vernunft, Andreas; Wensch-Dorendorf, Monika; Wolf, Petra; Metges, Cornelia C.; Zeyner, Annette
Abstract: Postprandial alterations of plasma amino acid (PAA) levels partly reflect a temporal contribution of the feed. How cereal grains affect PAA levels is not known. We hypothesized that a meal of cereal grains causes a temporal increase of PAA, affected by grain species, grain genotype and meal size. Six mares were used in three consecutive trials, receiving four oats, barley and maize genotypes, respectively. Individual grain genotypes were provided as 3 meal sizes corresponding to 1.0, 1.5 or 2.0 g starch/kg body weight. Meadow hay (1.5 kg/100 kg body weight) was offered daily. At the test days, 1 kg hay was fed 60 min prior to the grain meal. Blood samples were taken before grain feeding (0 min) and 30, 60, 90, 120, 180, 240 and 300 min thereafter. Subsequently, the remaining hay was offered. The genotype × starch quantity (i.e., meal size) interaction had a major effect on postprandial PAA concentrations ( P < 0.05). Availability of amino acids (AA), ingested from different grain genotypes, apparently differed at both the digestive and post-digestive level. Thus, AA supply from grain feeding can better be assessed on the genotype level. The concentrations of most PAA increased rapidly with a postprandial maximum at around 30 min. Hay feeding might have an underrated capability for AA provision because increases of PAA levels were initialized already by ingestion of a 1 kg hay. It remains unclear which portion of the PAA kinetics response originates from hay feeding and which one from the cereal grain meal. Highlights: Plasma amino acid (PAA) levels were elevated up to 1.8-fold after hay and a grain meal. The PAA meal responses were affected by grain species, grain genotype and meal size. The PAA response was fast (maximum levels were mostly reached after around 30 min). The contribution of hay to the increase of PAA levels needs clarification.